2010
DOI: 10.1177/000348941011900802
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Adenotonsillectomy for Obstructive Sleep Apnea Syndrome in Children

Abstract: Adenotonsillectomy is associated with improvements in PSG, behavior, and QOL in children with OSAS. However, it may not resolve OSAS in all children. The efficacy and role of additional therapeutic options require more study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
4
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 29 publications
5
78
4
3
Order By: Relevance
“…The meta-analysis reported that 88% of obese patients still had a postoperative AHI ≥1/hour, 75% had a postoperative AHI ≥2/hour, and 51% had a postoperative AHI ≥5/hour. Preoperative obesity was found to be a significant risk factor for postoperative residual OSAS in several other studies [133][134][135] as well, even when multivariable modeling was used to control for other factors such as age and preoperative AHI. The odds ratios of persistent OSAS in obese patients ranged in these models from 3.2 134 to 4.7.…”
Section: Obesitymentioning
confidence: 99%
See 3 more Smart Citations
“…The meta-analysis reported that 88% of obese patients still had a postoperative AHI ≥1/hour, 75% had a postoperative AHI ≥2/hour, and 51% had a postoperative AHI ≥5/hour. Preoperative obesity was found to be a significant risk factor for postoperative residual OSAS in several other studies [133][134][135] as well, even when multivariable modeling was used to control for other factors such as age and preoperative AHI. The odds ratios of persistent OSAS in obese patients ranged in these models from 3.2 134 to 4.7.…”
Section: Obesitymentioning
confidence: 99%
“…132 It is important to recognize that there are clearly recognizable risk factors for postoperative persistence of OSAS and that the prevalence of these risk factors in the populations studied had an important impact on their estimates of postoperative persistence of OSAS. For example, >50% of patients in the multicenter study of Bhattacharjee et al 133 were obese, whereas 21% of the patients in the series by Ye et al 134 were obese, defined as 95th percentile for the Chinese population. It should be emphasized that although many of these studies showed a high proportion of patients with residual OSAS after AT, most patients exhibited a marked decrease in AHI postoperatively.…”
Section: Postoperative Persistence Of Osas After Atmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that OSAS is multifactorial and alleviation of nasal obstruction is only a partial solution. Tonsillectomy and adenoidectomy in children with OSAS can result in complete resolution of symptoms but results are variable between studies with success rates of 27-87% reported (54,55). The use of nasal dilators has been examined in 5 studies and has provided equivocal results.…”
Section: Does Reversal Of Nasal Obstruction Also Reverse the Sleep DImentioning
confidence: 99%